Structural assessment for an old steel railway bridge under static and dynamic loads using fibre optic sensors - Lee, S.C. (ICE Publishing, 2019)
This article presents the structural assessment of an existing old steel railway bridge in Malaysia using fibre optic sensors. The steel bridge was built more than a century ago and the bridge structural drawings and other documentations were lost over the years. Keretapi Tanah Melayu Berhad (KTM), the Malaysian rail operator was upgrading the railway line to cater for heavier and faster locomotives. The bridge is subjected to a potential risk of structural health deterioration or fatigue due to corrosion and long service period in such a high humidity country. Full scale static and dynamic tests using locomotives were carried out to assess the structural integrity of the steel bridge. Two types of optical sensors were used. Discrete and distributed fibre optic sensors were mounted on critical steel panels to monitor the change in strain of these members under dynamic and static loads. The discrete sensor, Fibre Bragg Grating (FBG) strain sensors were able to measure the change in strain at 1000 Hz frequency, and were used during the dynamic test where a locomotive travelled through the bridge at maximum speed of 40 km/hour. Distributed fibre optic (DFOS) sensors were mounted on the bottom chord of the steel truss to measure the maximum tensile strain when the locomotive was placed at the centre of the bridge. The results from the two different fibre optic sensors (FBG and DFOS sensors) were then compared and the results showed good agreement to strain measurements. Â© International Conference on Smart Infrastructure and Construction 2019, ICSIC 2019: Driving Data-Informed Decision-Making.